Efeitos da oxigenação hiperbárica na formação de aderências após laparotomia em ratas - Simone Vargas Bento (2012)
Objective: to determine the effects of hyperbaric oxygenation in rats th at have undergone laparatomy after provocation and stimulation for adhesion formation. The frequency of the pos-operatory adherences, their characteristics, the parietal peritoneum histology, and the effects of pressure alteration and oxygen concentration were evaluated in each group. Method: 60 female rats of the Rattus novergicus species, strain Wistar, underwent general anesthesia with association of 70 mg/kg ketamine and 10 mg/kg xilazine through intramuscular via. After laparatomy, silk 2-0 points were performed in the peritoneal wall of the four abdominal quadrants and posterior cavity closure. The animals were distributed in three groups, group 1- control, group 2 underwent high pressures and environmental oxygenation, and group 3 underwent 100% hyperbaric oxygenation. Daily 120 minute sections have been carried out for six days. In the seventh day re-laparatomy was performed with the cavity opening photography and filming for the adherences rupture and evaluation; it was collected biopsies of the involved four quadrants peritoneum and the operation wound. The videos were watched and randomly evaluated by three surgeons and the biopsies were evaluated by anatomopatologist, both unaware of the groups to which the animals belonged. Results: the Fisher test was used to evaluate the adherences under macroscopy and the peritoneum in the microscopy evaluations. The statistically significant results were those that showed p<0,05. Group 3 had no difference related to group 1 concerning the adherences intensity (p=0,002) and cell proliferation (p=0,02) and in relation to group 2 in the same parameters, with p=0,01 and p=0,02, respectively. Conclusion: the results allowed to see that the hyperbaric oxygenation, although have no reduced the adherences frequency, acted in the reduction of their severity and in the vascular proliferation reduction. In this regard it could be concluded that the greater oxygen supply, through revascularization, was determinant in the adherences formation, characteristics and intensity.